2018
DOI: 10.18697/ajfand.81.16515
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and antinutritional evaluation of indigenous Ethiopian okra (Abelmoschus esculentus) seed accessions

Abstract: Okra, of high nutritional potential, is one of the underutilized indigenous vegetables in Ethiopia. A food based-intervention specifically dietary diversification is an affordable and sustainable strategy to meet the demand of adequate food supply and population growth. One way of ensuring dietary diversity is to search and promote underutilized indigenous plant species such as okra. Therefore, the objective of this study was to determine nutritional and anti-nutritional factors content of the seeds of eight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
3
15
6
Order By: Relevance
“…Also, the range of crude protein contents obtained for okra calyx flour were within the range (10.25-26.16%) reported for crude protein contents of okra flour by Gemede et al (2016). However, the values obtained for the crude protein contents of okra calyx flour were lower than that of okra seed flour of 41.11%, 22.14%, 18.96% and 22.51-38.09% reported by Adelakun et al (2009), Soares et al (2012), Dhruve et al (2015) and Habtamu et al (2018), respectively. Protein is responsible for the growth in children and restoration of tissue loss in human body (Obahiagbon and Erhabor, 2010; Gemede et al , 2016).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Also, the range of crude protein contents obtained for okra calyx flour were within the range (10.25-26.16%) reported for crude protein contents of okra flour by Gemede et al (2016). However, the values obtained for the crude protein contents of okra calyx flour were lower than that of okra seed flour of 41.11%, 22.14%, 18.96% and 22.51-38.09% reported by Adelakun et al (2009), Soares et al (2012), Dhruve et al (2015) and Habtamu et al (2018), respectively. Protein is responsible for the growth in children and restoration of tissue loss in human body (Obahiagbon and Erhabor, 2010; Gemede et al , 2016).…”
Section: Resultssupporting
confidence: 69%
“…The values of moisture content, ash, crude protein, crude fat, crude fibre and carbohydrate ranged 8.1-8.9%, 8.4-9.0%, 14.3-15.3%, 1.4-2.1%, 16.9-18.2% and 47.1-49.4%, respectively. The values obtained for the moisture contents of okra calyx flour were lower than that of okra seed flour of 10.38%, 13.99% and 9.27-12.70% reported by Adelakun et al (2009), Soares et al (2012) and Habtamu et al (2018), respectively. However, the moisture content of 5.52% and 6.31% reported for okra flour by Ndamitso et al (2012) and Ukegbu and Okereke (2013) were lower than that obtained for okra calyx flour.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have confirmed the role of potassium ions as the key element in the process of photosynthesis, protein synthesis, enzymatic activities and cellular metabolism whereas sodium plays an important role as vacuolar osmotic. Similarly, elevated phosphorus imparts a pivotal role in photosynthesis, carbohydrate metabolism and energy regulation (Habtamu et al, 2018;Gupta et al, 2019;Saheed, 2020).…”
Section: Okra Seed Priming Bymentioning
confidence: 99%
“…Various values have been previously reported for Amaranthus cruentus, Valcárcel-Yamani and Lannes [16] found ranged at 180.1 -217.0 mg/100g in amaranth seeds, Topwal [17] found Calcium ranged at 160 -212 mg/100g, Soriano-García et al [18] as 159 mg/100g. In case of Abelmoschus esculentus, Habtamu et al [19] found mean calcium content was 81.77 mg/100g which was similar to the present study and higher than those reported for okra seed by Ndangui et al [20] as 78.65 mg/100g, but lower than those reported as 112.50 -345.83 mg/100g [21]. In this study, the lowest calcium content found in Cucumis sativus (12±.36 mg/100g) which was less than Abbey et al [22] as 20.45 to 25.47 mg/100g.…”
Section: Content Of Calcium (Ca)mentioning
confidence: 99%